2002
DOI: 10.1002/jmv.10148
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of respiratory syncytial virus IgG antibodies in infants living in a rural area of Mozambique

Abstract: A case control study was carried out in Manhiça (Mozambique). Serum samples were collected from infants < 1 year of age in hospital to assess the effect of serum antibodies on the incidence of respiratory syncytial virus (RSV) infection. Sera were collected from a total of 31 cases of RSV infection and paired uninfected controls matched for age and sex. Anti-RSV antibodies were assessed by a membrane fluorescent antibody test (MFAT) for immunoglobulin G (IgG) antibodies and by a neutralizing antibody test. IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…The role of maternal antibodies in the transmission of hRSV at the population level is uncertain. It has been shown that higher levels of maternal antibodies are associated with increased protection from clinical infection [24], but this association is partial and probably short term (maternal antibodies are only present for 3-6 months [25]). For the purposes of the model presented, it is assumed that maternal antibodies have negligible effect on the transmission of the virus in the whole population.…”
Section: Model Structurementioning
confidence: 99%
“…The role of maternal antibodies in the transmission of hRSV at the population level is uncertain. It has been shown that higher levels of maternal antibodies are associated with increased protection from clinical infection [24], but this association is partial and probably short term (maternal antibodies are only present for 3-6 months [25]). For the purposes of the model presented, it is assumed that maternal antibodies have negligible effect on the transmission of the virus in the whole population.…”
Section: Model Structurementioning
confidence: 99%
“…Maternally-derived high affinity RSV-specific serum IgG antibody is the best known correlate of protection against infection in infants (Fig 2d) and it is assumed that the relative rarity of severe RSV disease in the first weeks of life is due to virus-specific maternally derived antibody 44,45,[63][64][65][66][67] . However, some of this protection may be indirect, due to reduced rates of maternal infection in those with high levels of antibody.…”
Section: Rsvmentioning
confidence: 99%
“…Nevertheless, severe RSV infection is consistently associated with low levels of pre-existing serum or cord blood RSV antibody 44,45,[63][64][65][66][67] . Infants in the top .…”
Section: Rsvmentioning
confidence: 99%
See 2 more Smart Citations